Animal-Assisted Therapy in Dementia: An Updated Literature Review - Alarcón-Braga, Esteban A. (2023)
Non-pharmacological interventions have shown to affect the symptoms of patients diagnosed with dementia. One of these interventions is animal-assisted therapy, which has been analyzed in multiple studies. However, the results of these interventions are mixed and no consensus has been reached. An electronic search was conducted in August 2021 in 4 databases (PubMed, Ovid Medline, Scopus, and Web of Science) to identify studies evaluating the role of animal-assisted therapy in patients diagnosed with dementia. The titles and abstracts of each article were independently analyzed. Subsequently, a full text of those articles that met the selection criteria was read. The narrative review was carried out based on the articles found. The effect of animal-assisted therapy on the psychiatric, psychological, and cognitive symptoms derived from dementia remains mixed and does not allow to draw specific conclusions. On the other hand, improvements have been observed in patients at a physical level and in terms of quality of life, since the patients showed a greater capacity when it comes to socializing, better communication skills, and greater motor skills. The published literature on the effects of animal-assisted therapy in patients with dementia is contradictory. A large number of articles claim to have found significant neurocognitive, motor, and quality of life improvements, while others claim not to have this effect.